Personal factors understood through the Ecological-Enactive Model of Disability and implications for rehabilitation research - Schwab, Sarah M.; Spencer, Caroline; Carver, Nicole S.; Andrade, Valéria; Dugan, Sarah; Greve, Kelly; Silva, Paula L. (Frontiers in Rehabilitation Sciences, 2022)
The International Classification of Functioning, Disability and Health (ICF) recognizes that disability arises from the interaction between an individual with a medical condition and the context in which they are embedded. Context in the ICF is comprised of environmental and personal factors. Personal factors, the background life and lifestyle of an individual, are poorly understood in rehabilitation. There is limited knowledge about how personal and environmental factors interact to shape the contextual conditions critical for explaining functioning and disability. In this paper, we explore how a newly proposed model of disability, the Ecological-Enactive Model of Disability, can enhance understanding of personal factors across multiple rehabilitation disciplines. We draw from a review of evidence and phenomenological interviews of individuals with Friedreich's Ataxia. We consider the practical impact of this understanding on disability and rehabilitation research and pathways for the future focusing on representative design.